The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/en12152959
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Refrigeration and Heat Pump Systems—A Comprehensive Review

Abstract: An increased awareness of the impacts of synthetic refrigerants on the environment has prompted the refrigeration industry and researchers worldwide to seek better alternatives in terms of technical, economic and environmental performance. CO2 refrigerant, also known as R744, has re-emerged as a potential alternative to existing refrigerants with its zero ozone depletion potential (ODP) and impressively low global warming potential (GWP). A refrigeration system utilising this refrigerant, however, suffers perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…While optimum gas cooler pressure, exit temperatures and suction superheat levels are reported in optimisation studies by Bruno et al [ 16 ] and others, these are interim variables in a physical model, controlled indirectly. They are affected by the heat pump hardware, gas charge levels, expansion valve settings and compressor speeds as well as ambient and target output temperatures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While optimum gas cooler pressure, exit temperatures and suction superheat levels are reported in optimisation studies by Bruno et al [ 16 ] and others, these are interim variables in a physical model, controlled indirectly. They are affected by the heat pump hardware, gas charge levels, expansion valve settings and compressor speeds as well as ambient and target output temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Significant research has been completed concerning the development and optimisation of transcritical CO 2 heat pumps with several helpful literature reviews published [ [14] , [15] , [16] , [17]] ]. However, the focus is often on refrigeration or water heating and only recently has there been significant research into using the heat pumps for space heating.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Baek et al [36], Ferrara et al [37], Kohsokabe et al [38], Ma et al [30] reported that the implementation of an expander unit, in replacement of the valve, leads to an improvement in COP of a CO 2 cycle under transcritical operation, in some cases similar to traditional heat pumps.…”
Section: Work Recovery Expandersmentioning
confidence: 99%
“…For the sake of keeping this study unbiased, two widely recognized ASHRAE standards are considered in order to define respectively thermal comfort and microclimate conditions: ANSI/ASHRAE Standard 55-thermal environmental conditions for human occupancy [16] (along with ISO 7730:2005 [17]) and the "Museums, Galleries, Archives and Libraries" chapter 21 in the American Society of Heating, Refrigeration, and Air Conditioning Engineers Inc. (ASHRAE) Handbook [18]. With regards to thermal comfort of people, it is an obvious assertion that the buildings do not need to be air conditioned for comfort in closure time when the visitors are not present.…”
Section: Energy Management In Historical Buildings and Museumsmentioning
confidence: 99%